Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11150-009-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

The labor supply effects of child care costs and wages in the presence of subsidies and the earned income tax credit

Abstract: Child care costs, Child care subsidies, EITC, Labor supply,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 47 publications
5
64
0
Order By: Relevance
“…Second, the QTE estimates for 1970 imply that the Lanham Act had negative effects on adult earnings starting at the 60th percentile. Such results are consistent with Havnes and Mogstad's (2015) QTE estimates for the Norwegian universal child care system, and they conform with recent US-based studies of pre-kindergarten programs (Cascio and Schanzenbach 2013) and nonparental child care arrangements (Herbst 2013), which uncover negative test score effects on children from more advantaged families.…”
Section: E Distributional Effects Of the Lanham Actsupporting
confidence: 89%
See 2 more Smart Citations
“…Second, the QTE estimates for 1970 imply that the Lanham Act had negative effects on adult earnings starting at the 60th percentile. Such results are consistent with Havnes and Mogstad's (2015) QTE estimates for the Norwegian universal child care system, and they conform with recent US-based studies of pre-kindergarten programs (Cascio and Schanzenbach 2013) and nonparental child care arrangements (Herbst 2013), which uncover negative test score effects on children from more advantaged families.…”
Section: E Distributional Effects Of the Lanham Actsupporting
confidence: 89%
“…The most common methodological approach to estimating price effects includes a discrete choice participation equation with selection-corrected predicted hourly child care expenditures and wages as the key right-hand-side variables. Results from these studies consistently point to a negative relationship between child care costs and mothers' employment (Anderson and Levine 2000;Connelly and Kimmel 2003;Tekin 2007a;Herbst 2010). However, the range of estimated own-price elasticities is quite large: 0.06 to 21.36.…”
Section: A Maternal Employmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, for single mothers. Herbst (2010) reports elasticities in the lower end of the reported elasticities above (-0.05). In a sample of studies, summarised in Blau (2003), the reported estimated elasticities range from 0.06 to -1.26.…”
Section: Introductionmentioning
confidence: 90%
“…The combined result of the reform saw a fall in child care costs and a rise in capacity. 2 There is a substantial literature on the importance of child care costs on the female labor supply over the last two decades (see for example, Blau & Robbins 1988;Ribar 1992;Connelly 1992;Connelly & Kimmel 2003;Blau & Tekin 2007;Gelbach 2002;Blau 2003;Baker, Gruber, & Milligan 2008;Lefebvre & Merrigan 2008;Herbst 2010;and Cascio 2009). Despite the large number of studies, considerable uncertainty lingers about the magnitude of the maternal employment effect with respect to the price of child care (Blau 2003).…”
Section: Introductionmentioning
confidence: 99%